Rancang Bangun Game Pembelajaran Operasi Dasar Matematika Menggunakan Algoritma Fisher Yattes - Yulyanto; Andriasnyah; Nunu Nugraha (Bulletin of Information Technology (BIT), 2023)
One of the lessons regarding basic mathematical operations is found in 2nd grade material of SD Negeri 2 Randusari. In the learning process the teacher has not maximized in utilizing existing technology, especially since grade 2 elementary school. The students still tend to like to play and mathematics is considered a difficult subject. Therefore it is necessary to utilize media to be able to attract students' interest with the learning while playing method. one of them with game media. In this game the researcher applies the Fisher Yattes algorithm to each question that comes out so that students are not monotonous in playing it. The Game Development Life Cycle (GDLC) is a guideline that regulates the process of making this game with development stages including initiation, pre-production, production, alpha testing, beta testing and release. The results of the UAT test on 14 students where this game can be accepted by users by getting an average percentage value of 89.64%. In its application the Fisher Yattes algorithm succeeded in generating random values in the game and no similar questions came out repeatedly at the same level.